Mewujudkan Kesejahteraan Masyarakat: Masyarakat Kuat, Negara Kuat, Mengapa Tidak? - Soetomo, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2008)
Welfare is one of many states obligations. Nevertheless, it is not only state activity which influences or promotes welfare. For this reason, every stakeholder: state, society and private business has role to promote welfare. Beside that, every stakeholder also has its strength and weakness. Therefore, cooperation among the stakeholder for their activity to promote welfare will produce more effective result. Through cooperation among stakeholder can produce supplementary and complementary activity in social services